Method for Correction of Design Diacoptic Z-Matrix of Complicated Power System - N. P. Badalyan (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper proposes correction method of a design diacoptic Z-matrix of complicated power system that ensures high manoeuvrability while calculating steady - state conditions.